1999
DOI: 10.1093/ndt/14.9.2137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of β2-microglobulin expression in different human cell lines by proinflammatory cytokines

Abstract: The present study provides evidence that interferons are important regulators of beta2M expression. It also shows that proinflammatory monocytic cytokines do not modulate directly the expression of beta2M in cells of hepatic, monocytic and T-lymphocytic origin. Whether they influence beta2M synthesis and secretion indirectly by modulating interferon synthesis needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…6 Serum b 2 M indicates the clearance of middle molecules by HD, or may be related to inflammation, as suggested by some authorities. 22,23 Accumulation of b 2 M leads to dialysis-related amyloidosis, which usually becomes apparent after several years of HD. However, a postmortem study showed that b 2 M amyloid deposition occurs in 21% of cases within 2 years and in 33% within 4 years after initiation of HD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Serum b 2 M indicates the clearance of middle molecules by HD, or may be related to inflammation, as suggested by some authorities. 22,23 Accumulation of b 2 M leads to dialysis-related amyloidosis, which usually becomes apparent after several years of HD. However, a postmortem study showed that b 2 M amyloid deposition occurs in 21% of cases within 2 years and in 33% within 4 years after initiation of HD.…”
Section: Discussionmentioning
confidence: 99%
“…7 A correlation between an inflammatory response during hemodialysis and elevated serum B2M has been already described. 8 Increased levels of B2M are seen in patients with hematologic and autoimmune disorders 9,10 but also seem to be elevated under conditions of high cell turnover, ischemia, or cardiomyopathy. 11,12 In 1 study in uremic patients on hemodialysis, B2M was related to carotid intima-media thickness.…”
mentioning
confidence: 99%
“…Taking into account that PCT is considered a marker of infection, [7][8][9]16,17,23] the correlation of B 2 -m to PCT is most likely attributed to the expression and production of these two substances from activated cells (i.e., monocytes, macrophages, lymphocytes). [5,17,24,25] This activation can be due to the secretion of cytokines and interferons during the immune response in the setting of pro-inflammatory substances release syndrome. Though this release can be provoked by infections or non-infectious conditions (e.g., contact of blood with bioincompatible membranes), the lack of correlation between B 2 -m to CRP, an accepted marker of systemic inflammatory reaction, [10][11][12] in all time periods points to the simultaneous production and release of B 2 -m and PCT only (or mostly) by infections.…”
Section: Discussionmentioning
confidence: 99%